TECHNICAL VOCATIONAL EDUCATION IN BRAZIL: THE CONTRACTORS’ PERCEPTIONS - Rocha-Pinto, Sandra Regina da; Cherman, Andrea; Bezerra, Katia Regina (Journal of Technical Education and Training, 2013)
The present study aims to addresses the development of technical skills in fulfilling the needs of the labor market. Essentially qualitative, the field research was conducted from October 2010 to June 2011. Fourteen professionals who had graduated from technical schools of different locations in the Rio de Janeiro were interviewed. Additionally, interviews were conducted with a): four leaders of the professional teams, who reported their expectations and difficulties in developing new professional in face of the demands on the day to day business, b): three humans resource professionals who exposed the difficulties of attracting and retaining those professionals. Due to their phenomenographic perspective, declarations by the interviewees were analyzed, interpreted and grouped according to meanings. This procedure made possible the generation of categories according to two types of perspectives: a) contracted parties: professionals who had graduated from technical schools; b) contracting parties: professionals responsible for hiring or managers those who had graduated from technical schools. The findings indicate that contractors perceive the school distant from the professional market both in physical and in conceptual terms. On the other hand, the contracted party reveals that entry in schools for professionalizing education is justified inasmuch as it has to do with a fast professional training.